Evaluate: (2x^3-3x^2-12x-20)/(2x+5)

Expression: $\frac{2x^{3}-3x^{2}-12x-20}{2x+5}$

Divide $ \frac{2x^{3}-3x^{2}-12x-20}{2x+5}:{\quad}\frac{2x^{3}-3x^{2}-12x-20}{2x+5}=x^{2}+\frac{-8x^{2}-12x-20}{2x+5}$

$=x^{2}+\frac{-8x^{2}-12x-20}{2x+5}$

Divide $ \frac{-8x^{2}-12x-20}{2x+5}:{\quad}\frac{-8x^{2}-12x-20}{2x+5}=-4x+\frac{8x-20}{2x+5}$

$=x^{2}-4x+\frac{8x-20}{2x+5}$

Divide $ \frac{8x-20}{2x+5}:{\quad}\frac{8x-20}{2x+5}=4+\frac{-40}{2x+5}$

$=x^{2}-4x+4+\frac{-40}{2x+5}$

Simplify

$=x^{2}-4x+4-\frac{40}{2x+5}$